Lactic acid as an invaluable green solvent for ultrasound-assisted scalable synthesis of pyrrole derivatives - Wang, Shi-Fan; Guo, Chao-Lun; Cui, Ke-ke; Zhu, Yan-Ting; Ding, Jun-Xiong; Zou, Xin-Yue; Li, Yi-Hang (Ultrasonics sonochemistry, 2015)
Lactic acid has been used as a bio-based green solvent to study the ultrasound-assisted scale-up synthesis. We report here, for the first time, on the novel and scalable process for synthesis of pyrrole derivatives in lactic acid solvent under ultrasonic radiation. Eighteen pyrrole derivatives have been synthesized in lactic acid solvent under ultrasonic radiation and characterized by 1H NMR, IR, ESI MS. The results show, under ultrasonic radiation, lactic acid solvent can overcome the scale-up challenges and exhibited many advantages, such as bio-based origin, shorter reaction time, lower volatility, higher yields, and ease of isolating the products.